THE INFLUENCE OF EMOTIONAL QUOTIENT, INTERPERSONAL COMMUNICATION, AND ORGANIZATIONAL COMMITMENT TOWARD ORGANIZATIONAL CONFLICT MANAGEMENT ON BANKING STRUCTURE IN INDONESIA - Hutagalung, Inge (IJRDO - Journal of Social Science and Humanities Research, 2017)
This research aims to analyze the management of conflict in a banking-work structure in the Indonesian, a highly collective-culture society. The research proves that conflict management is not only influenced by the psychological aspect (emotional quotient, organizational commitment) but also by the aspect of communication (i.e., interpersonal communication). The study’s participants consisted of permanent employees in a state-owned bank with a sample of 200 people. The relationship test variables were used in Structural Equation Modeling. The data was collected from a questionnaire using a Likert scale. Based on research result, the researcher concluded that organizational commitment has a stronger influence on the management of organizational conflict than emotional quotient and interpersonal communication. Responding to the influence of organizational commitment on organizational conflict management, the researcher assumed that this condition occurs because the object of research has normative commitment. Normative commitment has been found to be associated with feelings of employees towards their obligation to remain in the organization.